Examining Predictors and Mediators of Vulnerability to Telecommunications Fraud among Senior Citizens in Taiwan - Ying Chia Hsu; Ran Wei (International Telecommunications Society (ITS), 2017)
Advances in telecommunications technologies such as the online voice and video calling, smart phones, and micro messaging service have not only made life easier for millions of users, they also strengthened their social ties and improved their psychological well-being. On the other hand, potential risks of being defrauded go hand in hand with the social and psychological benefits of advanced telecommunications technologies in the mobile era. To respond to the pressing need for a better understanding of how fraudulent telecommunications occur, this study seeks to examine predictors and mediators of the vulnerability of seniors to telecommunications fraud with a focus on the role of calling behaviors, social presence, trust, perceived dependence, and perceived importance in telecommunications technology. Results show that 4 factors play essential roles in telecommunication among seniors. Implications of the findings for telecommunications policymaking are discussed.
Keywords: 330; telecommunications fraud; telephony; mobile phones; text messages; social presence; trust; senior citizens; Taiwan